Carbenes trapping on Aluminum-Magnesium surface implanted with Silicon, Germanium, Tin: Promising of semiconductors by molecular modeling approach - Mollaamin, Fatemeh; Monajjemi, Majid (Art and Science Press Pte. Ltd., 2023)
Al-Mg surface doped silicon, germanium and tin is theoretically studied using first-principles density functional theory (DFT) at the CAM-B3LYP/EPR-III, LANL2DZ,6-31+G(d,p) level of theory to explore the chemical adsorption and corrosion inhibition of organic carbenes through coating process. The fluctuation of NQR is estimated the inhibiting role of pyridine and its derivatives (picoline, 3-picoline,4-picoline,2,4-lutidine) for (Si, Ge, Sn)-doped Al-Mg alloy nanosheet due to concerning nitrogen in the benzene ring of related heterocyclic compounds becoming close to the monolayer nanosurface of Al-Mg-X (X = Si, Ge, Sn) nanoalloys. The NMR spectroscopy remarks that (Si, Ge, Sn)-doped Al-Mg alloy nanosheet has maximum band wavelengths approximately between 10 ppm–2000 ppm accompanying the sharpest peaks for inhibitors → Al-Mg-X which are between 10 ppm–100 ppm. IR spectroscopy has exhibited that (Si, Ge, Sn)-doped Al-Mg alloy nanosheet with the fluctuation in the frequency of intra-atomic interaction leads us to the most influence in the vicinage atoms generated due to inter-atomic interaction. The maximum IR spectrum for complexes of [inhibitor → Al-Mg-X (X = Si, Ge, Sn)] is observed in the frequency range between 500 cm−1–3500 cm−1. This work exhibits that proper monitoring of the coating mechanism by Langmuir adsorption can illustrate inhibiting the aluminum nanoalloys corrosion through an investigation of their structural and thermodynamic properties. This work investigates the characteristics, band structure, and projected density of state (PDOS) of Al-Mg nanoalloy doped with Si, Ge, Sn elements for increasing the corrosion inhibition of the surface through adsorption of organic molecules of carbenes in the surface coatings process. This article can be helpful in a range of applications which uses Al-Mg alloy for the study of energy storage and adsorption of air pollution or water contamination. Many different approaches such as surface coatings, alloying and doping can be adopted to protect the surface.
Keywords: 13. Climate action; 7. Clean energy